A novel dynamic electromagnetic tracking navigation system for distal locking of intramedullary nails. (September 2021) - Gao, Yao; Wang, Huixiang; Tu, Puxun; Hu, Junlei; Wang, Qiugen; Chen, Xiaojun
Highlights: An efficient, reproducible and user-friendly registration method based on external landmarks was proposed for most commercial interlocking intramedullary nails. This work has introduced a novel calibration method for hand-held guiders named. double calibration to realize real-time visualization of its aim poses. A feasible and efficient EM tracking method to the applications in the distal screw holes preparation of IM nails has been experimentally demonstrated and proven through puncture, model and cadaver experiments. Abstract: Background: The accurate distal locking of intramedullary (IM) nails is a clinical challenge for surgeons. Although many navigation systems have been developed, a real-time guide method with free radiation exposure, better user convenience, and high cost performance has not been proposed. Methods: This paper aims to develop an electromagnetic navigation system named TianXuan-MDTS that provides surgeons with a proven surgical solution. And the registration method with external landmarks for IM nails and calibration algorithm for guiders were proposed. A puncture experiment, model experiments measured by 3D Slicer and cadaver experiments (2 cadaveric leg specimens and 6 drilling operations) are conducted to evaluate its performance and stability. Results: The registration deviations (TRE) is 1.05± 0.13 mm. In the puncture experiment, a success rate of 96% can be achieved in 45.94 s. TianXuan-MDTS were evaluated on 3 tibia model. The results demonstrated that all 9 screw holes were successfully prepared at a rate of 100% in 91.67 s. And the entry point, end point, and angular deviations were 1.60±0.20 mm, 1.47±0.18 mm, and 3.10±0.84°, respectively. Postoperative fluoroscopy in cadaver experiments showed that all drills were in the distal locking holes, with a success rate of 100% and the average time 143.17± 18.27 s. Conclusions: The experimental results indicate that our system with novel registration and calibration methods could serve as a feasible and promising tool to assist surgeons during distal locking.